Peripheral Ameloblastoma of Palatal Mucosa: A Rare Case Report and Literature Review - Namdar Pekiner, Filiz; Ünal, Suay Yağmur; Yülek, Hakan; Keser, Gaye (UI Scholars Hub, 2024)
Peripheral ameloblastoma (PA), an uncommon and unique form of odontogenic tumor, accounts for around 2-10% of all ameloblastomas. The extraosseous position is the distinguishing aspect of this form of tumor, which is otherwise comparable to a typical ameloblastoma. As late recurrence is also recorded, continuous follow-up is required. A case of peripheral ameloblastoma in a 23-year-old male that affected the right posterior palatal mucosa was presented in this case study. A 23-year-old male patient had an exophytic mass located at the junction of the hard and soft palate, in the palatal neighborhood of the tooth number 18. An excisional biopsy of the lesion was performed under local anesthesia, and the final diagnosis showed peripheral ameloblastoma. An appointment for intermittent controls was scheduled in case of a recurrence. PA arises at a much younger age than intraosseous ameloblastoma. It is an exophytic growth in the soft tissues overlaying the tooth-bearing portions of the jaws, with fibrous epulis being the most common first diagnosis. Conservative supraperiosteal surgical excision with appropriate disease-free margins is the current therapy of choice.